Green Marketing And Purchasing Decisions Of Female College Students ' Cosmetics Products - Setyadi, Bakti; Helmi, Sulaiman; Sofyan, Yayan (UNIVERSITAS PAKUAN, 2024)
In recent decades, awareness of the importance of environmental conservation has increased significantly. One sector that has received great attention is the cosmetics industry, which is known to have a significant impact on the environment due to the use of hazardous chemicals and environmentally unfriendly production processes. Therefore, the concept of green marketing is becoming increasingly relevant. Green marketing is a marketing strategy that emphasizes sustainability and environmental awareness, with the use of environmentally friendly materials, recyclable packaging, and promotion of the environmental benefits of the product. The urgency of this research is very high considering the increasing environmental awareness among consumers, especially among the younger generation. This study adopts a qualitative approach with a case study method. The qualitative approach was chosen because it allows researchers to dig into an in-depth understanding of Green Marketing and its influence on brand perception among female students. The case study method is used because it provides an opportunity to collect rich and in-depth data from the perspective of the individual who is the focus of the study. This study involved 15 informants from the female student community, who were selected based on inclusion criteria as active students in various study programs. This study shows that green marketing has a significant influence on cosmetic purchasing decisions by female students. Environmental awareness and preference for environmentally friendly products are important factors in their choices. Informants showed a good understanding of environmentally friendly cosmetic products and tended to choose brands that practice sustainability for ethical reasons, such as environmental protection, animal welfare, and workers' rights. Informative advertising and promotions also played an important role in increasing awareness and trust in these products, supporting the finding that green Effective marketing can change consumer perceptions and behavior.